Supply chain involvement in business continuity management: effects on reputational and operational damage containment from supply chain disruptions. Issue 6 (27th May 2020) - Azadegan, Arash; Syed, Tahir Abbas; Blome, Constantin; Tajeddini, Kayhan
Abstract : Purpose: Does internal integration extend to business continuity and to managing supply chain disruptions (SCDs)? Despite the voluminous literature on supply chain integration, evidence on its effectiveness on risk management and disruption response is scant. The purpose of this paper is to assess the effectiveness of business continuity management (BCM) and of supply chain involvement in BCM (SCiBCM) on reputational and operational damage containment in the face of SCDs. Design/methodology/approach: This study draws on Simons' Levers of Control framework to explain how the involvement of supply chain in BCM affects firm capabilities in containing damages caused by major SCDs. The authors develop and test hypotheses by analyzing large-scale questionnaire responses from 448 European companies. Findings: Results of the data analysis suggest that BCM improves reputational damage containment, whereas SCiBCM improves operational damage containment. The findings also show that the significant effects of BCM and SCiBCM on reputational and operational damage containment, respectively, were amplified for the firms facing higher supply chain vulnerability. Post-hoc analysis further reveals the complementarity effect between BCM and SCiBCM for the companies exposed to high supply chain vulnerability. Originality/value: Evidence on the effects of BCM and its internal integration on performance is limited. This study offers empirical evidence on the topic. Also, while supply chain integration can improve information sharing and coordination, some may not fully recognize its potential benefits in addressing SCDs. This study theoretically and empirically demonstrates the role played by internal integration, in the form of SCiBCM, in improving organizational damage containment efforts.